Inflation and Disinflation in Turkey - Aykut Kibritçioğlu; Libby Rittenberg; Faruk Selçuk; O. Cevdet Akçay; C. Emre Alper; M. Hakan Berument; Selahattin Dibooğlu; Haluk Erlat; Ahmet Ertuğrul; N. Kamuran Malatyalı; Tevfik F. Nas; Süleyman Özmucur; et al. (Ashgate, 2002)
Based on its outward-oriented development strategy, respectable growth, increased integration into world trade and financial markets, and imperfect though vibrant and wide-based democracy, Turkey is often cited as a development model for other countries in the region and elsewhere. Countering this positive picture of the Turkish economy over the last two decades, however, is the incompleteness of its reform process: the boom-bust nature of its growth, persistently high inflation, delays in privatising state-owned enterprises, and high and persistent government budget deficits. In January 2000 Turkey embarked on an ambitious IMF-backed stabilization program designed to correct the weaknesses in its economy, and, in particular, to reduce inflation to single digits by the end of 2002. Since then, though, Turkey has experienced two financial crises and redesigned its stabilization program to bring inflation down more gradually. This collection analyzes the nature of Turkey's inflation and the likely costs and benefits of disinflation.
Keywords: E31; E60; P44; E50; C20; C30; 330; inflation; disinflation; Turkey; Turkish economy; budget deficit; monetary policy; central bank; inflationary expectations; Inflation; Anti-inflation policy; Inflation expectations; Inflation rate; Turkey; Monetary policy; Budget deficit; Central bank; Inflation expectations